Penggunaan Metafora sebagai Frame Pencetus Unsur Humor dalam Kamigata Rakugo â€œTachigire Senkooâ€ dan â€œSutokuinâ€ - Novianti, Nalti (Bina Nusantara University, 2010)
The use of metaphor in a comedy story is a tool to create the funny effect. In many comedy stories of kamigata rakugo, a metaphor can be used as one way to bring the contradict frame that will cause the unbalance in the story (incongruity). It means that the comedy story cannot stand alone without any contradiction of situation. This contradiction of situation is brought up by the story teller to get one phrase that is able to attract the listeners? attention, and in the end will bring a big laughs.